2011
DOI: 10.1007/s10554-010-9777-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between high density lipoprotein-cholesterol and remodeling index in patients with coronary artery disease: IDEAS (IVUS diagnostic evaluation of atherosclerosis in Singapore)-HDL study

Abstract: Serum level of high density lipoprotein (HDL)-cholesterol is associated with risk of coronary artery disease. We correlated the serum level of cholesterol with coronary artery remodeling index of patients with coronary artery disease. A total of 120 patients with de novo lesions located in native coronary artery were studied. Remodeling index was based on intravascular ultrasound (IVUS) interrogation of the lesions using the static approach, and was defined as external elastic membrane (EEM) area at lesion/ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Indeed, earlier reports have produced conflicting results on the relationship between HDL-C levels and coronary artery remodeling. [25][26][27] In the present study, we observed that remodeling index (0.96 AE 0.18 vs. 0.97 AE 0.18, P ¼ 0.70) and positive remodeling percentage (31.7% vs. 35.0%, P ¼ 0.84) were similar between the low HDL-C and high HDL-C groups. Moreover, a significant correlation between HDL-C levels and remodeling index was not found.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Indeed, earlier reports have produced conflicting results on the relationship between HDL-C levels and coronary artery remodeling. [25][26][27] In the present study, we observed that remodeling index (0.96 AE 0.18 vs. 0.97 AE 0.18, P ¼ 0.70) and positive remodeling percentage (31.7% vs. 35.0%, P ¼ 0.84) were similar between the low HDL-C and high HDL-C groups. Moreover, a significant correlation between HDL-C levels and remodeling index was not found.…”
Section: Discussionsupporting
confidence: 58%
“…However, arterial remodeling is a heterogeneous process and the mechanism by which HDL‐C influences arterial remodeling is not well known. Indeed, earlier reports have produced conflicting results on the relationship between HDL‐C levels and coronary artery remodeling . In the present study, we observed that remodeling index (0.96 ± 0.18 vs. 0.97 ± 0.18, P = 0.70) and positive remodeling percentage (31.7% vs. 35.0%, P = 0.84) were similar between the low HDL‐C and high HDL‐C groups.…”
Section: Discussionsupporting
confidence: 48%
“…Lee et al (16), had reported that HDL-cholesterol level was negatively correlated with coronary remodeling index, implying that coronary arteries tend to develop a positive remodeling pattern as serum level of HDL-cholesterol decreases. When stratified according to diabetic status of the patients, the negative correlation between HDL-cholesterol and the remodeling index was only observed in nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of atherosclerosis contributes strongly to the differentiation of monocytes into macrophages, which accumulate cholesterol to form foam cells in the vessel wall . High‐density lipoprotein (HDL) plays a key role in protecting against atherosclerosis, mainly through reverse cholesterol transport (RCT), a process in which excess cholesterol is carried from the arterial wall back to the liver . The RCT pathway is currently considered to be the only mechanism by which the human body clears away excess cholesterol .…”
Section: Introductionmentioning
confidence: 99%
“…High‐density lipoprotein (HDL) plays a key role in protecting against atherosclerosis, mainly through reverse cholesterol transport (RCT), a process in which excess cholesterol is carried from the arterial wall back to the liver . The RCT pathway is currently considered to be the only mechanism by which the human body clears away excess cholesterol . Adenosine triphosphate‐binding cassette (ABC)A1 and ABCG1, which are members of the ABC transporter superfamily, are considered to mediate the active efflux of cholesterol to lipoprotein acceptors to promote RCT.…”
Section: Introductionmentioning
confidence: 99%